Product Market Imperfections and Loan Commitments - MAKSIMOVIC, VOJISLAV (Journal of Finance, 1990)
ABSTRACT I show in a model of competitive banks that the characteristics of loan contracts are affected by product market imperfections in the borrower's industry. A bank loan commitment increases the value of a borrower firm operating in an imperfectly competitive industry and thus dominates a simple loan even in the absence of risk sharing considerations and informational asymmetries between the borrower and the bank. While it is individually rational for a firm to obtain a loan commitment, all the firms in that industry taken together are made worse off by the existence of loan commitments.